2017
DOI: 10.1080/17843286.2017.1361622
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins modify relapsing membranous glomerulonephritis after kidney transplantation: a case report

Abstract: This case illustrates that immunoglobulins had long-lasting effects on the renal transplant although the glomerulonephritis had been resistant to other lines of therapy before transplant. We advocate that the use of immunoglobulins as a rescue therapy in refractory idiopathic membranous glomerulonephritis should be further investigated. Presently, existing evidence only comes from retrospective data and non-randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, the effect of the tumour microenvironment on the stemness of thyroid cancer cells is unclear. Tumour-associated macrophages (TAMs) are vital immune cells in the tumour microenvironment that have been shown to be associated with poor prognosis in a variety of malignant tumours ( 12 , 13 ), especially M2-like TAMs, which directly communicate with CSCs to promote their stemness and/or subsequent oncogenic properties, thereby triggering tumour invasion and metastasis ( 14 , 15 ). Therefore, the present study focused on investigating the role of M2-like TAMs in cancer stemness and thyroid cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the tumour microenvironment on the stemness of thyroid cancer cells is unclear. Tumour-associated macrophages (TAMs) are vital immune cells in the tumour microenvironment that have been shown to be associated with poor prognosis in a variety of malignant tumours ( 12 , 13 ), especially M2-like TAMs, which directly communicate with CSCs to promote their stemness and/or subsequent oncogenic properties, thereby triggering tumour invasion and metastasis ( 14 , 15 ). Therefore, the present study focused on investigating the role of M2-like TAMs in cancer stemness and thyroid cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Membranous glomerulonephritis (MGN) is one of the major autoimmune-mediated nephrotic syndrome that affects mainly the adult population 1,2. MGN shows the symptoms of immune complex deposition in glomerular subepithelial space and heavy proteinuria 3,4. The major complications associated with MGN are chronic inflammation, oxidative stress, glomerular and tubulointerstitial lesions 5.…”
Section: Introductionmentioning
confidence: 99%
“…Membranous glomerulonephritis (MGN) is one of immune-mediated and more common forms of nephrotic syndrome in the adult population [ 1 , 2 ]. MGN shows a special type of immune complex glomerulonephritis and had the symptoms of glomerular subepithelial IgG-containing immune complex deposits and usually heavy proteinuria [ 3 , 4 ]. Previous study had confirmed that primary MGN is an autoimmune disease and M-type phospholipase A2 receptor (PLA2R) is a major specific antibody in this disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%